Food and Beverage Business Development Strategy at Time Depot to AET Surabaya - Ervina Yulia Angkat; Zuhrinal M Nawawi (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The more advanced era and changes in human life patterns cause human needs to change, especially primary needs, one of which is food and drink. The food and beverage industry is very developed and varies in terms of prices and types. From that, business competition in the culinary field is very tight and affects the food and beverage industry from producers to consumers. This research was conducted to find out how the right business development strategy uses internal environmental analysis from the perspective of resources, remote external & industry, enhanced by a business plan. The study used primary qualitative data from the object of research and secondary from literature studies obtained through interviews and documentation. Followed by data reduction, data presentation, and ended with data verification. Data analysis used triangulation validity test and member check for validity. The result of this research is a change in strategy to focus on specific market niches accompanied by a simple business plan that replaces the cost leadership strategy that has been proven to have been implemented so far by the object of research.